LEXICAL RELATIONS AND CONTEXTUAL MEANING ANALYSIS OF SURAH AL-KAHF IN ABDULLAH YUSUF ALI’S ENGLISH TRANSLATION - Maulidya, Savira Rahma; Ghozali, Muhamad Afifuddin; Hutagalung, Khairulman Akbar (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2024)
Direct translation of the Arabic Qur'an to other languages exists with the closest literal meaning due to the several absences of the exact equivalent meanings of words. Abdullah Yusuf Ali did one of the popular translation works from Arabic to English. One translation issue is the translator's bias, which leads this study to analyze the linguistic relations and contextual meanings in the English Qur'an translation to disclose the bias issue within and enclose prejudication arose. This qualitative study used the mixed technique of semantic analysis in four steps. The data of this research is the English translation of Chapter Al-Kahf (The Cave) verses 65-82 by Abdullah Yusuf Ali. The results of this study enclosed four types of lexical relations and four types of contextual meaning. Also, this study unintentionally found that the synonymy and antonymy pair categories consist of one verse pair and a different verse pair. Uniquely, a category of homonymy and five unrevealed patterns of contextual meaning used are also found in this study. This study concluded that the English translation of the Qur'an, Chapter Al-Kahf verses 65-82 by Abdullah Yusuf Ali has used several procedures to preserve the message within the Qur'an from being misinterpreted by the reader.